Calcifiers can Adjust Shell Building at the Nanoscale to Resist Ocean Acidification. Issue 37 (9th August 2020) - Leung, Jonathan Y. S.; Chen, Yujie; Nagelkerken, Ivan; Zhang, Sam; Xie, Zonghan; Connell, Sean D.
Abstract: Ocean acidification is considered detrimental to marine calcifiers based on laboratory studies showing that increased seawater acidity weakens their ability to build calcareous shells needed for growth and protection. In the natural environment, however, the effects of ocean acidification are subject to ecological and evolutionary processes that may allow calcifiers to buffer or reverse these short‐term negative effects through adaptive mechanisms. Using marine snails inhabiting a naturally CO2 ‐enriched environment over multiple generations, it is discovered herein that they build more durable shells (i.e., mechanically more resilient) by adjusting the building blocks of their shells (i.e., calcium carbonate crystals), such as atomic rearrangement to reduce nanotwin thickness and increased incorporation of organic matter. However, these adaptive adjustments to future levels of ocean acidification (year 2100) are eroded at extreme CO2 concentrations, leading to construction of more fragile shells. The discovery of adaptive mechanisms of shell building at the nanoscale provides a new perspective on why some calcifiers may thrive and others collapse in acidifying oceans, and highlights the inherent adaptability that some species possess in adjusting to human‐caused environmental change. Abstract : Ocean acidification is expected to weaken the mechanical strength of shells built by marine calcifiers. In contrast to this common belief, it is demonstrated herein that a calcifier can build more durable shells through nanoscale adjustments of calcium carbonate crystals, such as crystal and nanotwin thickness. This discovery opens opportunities to explore the capacity of calcifiers to adapt to ocean acidification.